A ghost in shining armor - Beharrie, Therese (Zebra Books/Kensington Publishing Corp., 2022)
Once haunted ... Gemma Daniels has never been quite the "down to earth" woman her adoptive parents raised her to be. She even has a unique gift: she can see ghosts--and she likes helping them settle their unfinished business. But the hotter-than-hot stranger she impulsively kisses on a bet is not only a phantom, he's determined to help her. And the only way Gemma can explain his presence is to pretend they're a real-life couple ... Twice shy ... Levi Walker lived--and died--to save his sister. Now he's got a second chance at life if he assists Gemma in reuniting with her own long-lost sibling ... and then never sees Gemma again. But as he starts to enjoy her irrepressible personality, he's finding it hard to abide by any rules at all ... Third time's the unforgettable charm ... Gemma is thrilled to be getting to know her sister, but it causes a family rift she may not be able to heal. On top of that, she's falling for a ghost with a dilemma. For Levi must decide what loyalty--and living--is truly all about. To fix their mistakes, Gemma and Levi must risk being real with themselves--and each other--if they're ever to claim true love ...